การใช้การคิดเชิงออกแบบเพื่อพัฒนาโมไบล์แอปพลิเคชันของธุรกิจแลกเปลี่ยนเสื้อผ้า - พัทธมน ยงบุญเนียม (จุฬาลงกรณ์มหาวิทยาลัย, 2023)
Fashion industry is one of the largest industries in the world. There is an increase in the production of accumulated clothing. With a simple production process can produce a lot and quickly respond to the purchasing needs of consumers. Clothing production has a negative impact on the environment from the beginning of the process until the end of the process. In addition to environmental problems There are also labor problems that arise. One of the solutions is "Circular Fashion," using recycled materials to make new clothes, renting, reselling  or exchange clothes so that consumers can recycle clothes that are no longer in use to make them more useful. This special project adopts design thinking in analysis and design process to develop a system that can truly solve their problems. As a result, suggestions and recommendations received from target users for the development of the system are useful and relevant to the project. The prototype obtained from this project will be a guideline for the development of mobile applications for the clothing exchange business. To help create a more sustainable approach to the clothing cycle. and help the world in another way.